2022
DOI: 10.3390/ijerph19137657
|View full text |Cite
|
Sign up to set email alerts
|

Parental Support and Problematic Smartphone Use: A Serial Mediating Model of Self-Esteem and Fear of Missing Out

Abstract: Based on problem behavior theory and interpersonal acceptance–rejection theory, this study aimed to examine the mediating roles of self-esteem and fear of missing out (FoMO) on the influence of parental support on adolescents’ problematic smartphone use. This study is a cross-sectional and descriptive study. A total of 260 Korean adolescents from two public middle schools were selected through convenience sampling (female, 50.4%; mean age, 13.16 ± 0.84; range age, 12~15). Participants completed self-report que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
9
0
3
Order By: Relevance
“…Since they are not afraid of peer rejection, they are more resistant to peer pressure on mobile phone use. In addition, prior research has also found that people with low self-esteem have a high fear of missing, and they are more afraid of missing information on social network sites ( 48 , 49 ), which promotes them to use social network sites very frequently. High self-esteem helps adolescents reduce the fear of missing out ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since they are not afraid of peer rejection, they are more resistant to peer pressure on mobile phone use. In addition, prior research has also found that people with low self-esteem have a high fear of missing, and they are more afraid of missing information on social network sites ( 48 , 49 ), which promotes them to use social network sites very frequently. High self-esteem helps adolescents reduce the fear of missing out ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior research has also found that people with low self-esteem have a high fear of missing, and they are more afraid of missing information on social network sites ( 48 , 49 ), which promotes them to use social network sites very frequently. High self-esteem helps adolescents reduce the fear of missing out ( 48 ). Adolescents with high levels of self-esteem will not pay too much attention to the information on social network sites, which will reduce the risk of mobile social media addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of demographic variables in consideration was conducted using an independent sample t -test and one-way ANOVA, e.g., [ 47 , 48 ]. One-way ANOVA was employed to assess the dissimilarities between the social identity scale, the school adaptation scale, the core self-evaluation scale, and the MMHI-60 scale among different demographic characteristics (i.e., migration time and grade).…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, FOMO has for instance been associated with development of problematic usage of a number of internet applications, including problematic internet usage (Röttinger et al, 2021) and smartphone addiction (Alinejad, Parizad, Yarmohammadi, & Radfar, 2022). However, on the other hand, an increasing number of studies underscore the role of social and self-related cognitions in this association such that the association between FOMO and smartphone addiction is mediated by loneliness (Alinejad et al, 2022) while FOMO mediates the association between parental support, self-construal, self-concept clarity or interpersonal sensitivity with problematic smartphone use (Kim, 2022; Lin et al, 2021; Servidio, Sinatra, Griffiths, & Monacis, 2021).…”
Section: Discussionmentioning
confidence: 99%